The impact of students’ mathematical attitudes on intentions, behavioral engagement, and mathematical performance in the China’s context - Wang, Limei; Peng, Fuqiang; Song, Naiqing (Frontiers in Psychology, 2022)
Referring to the theory of planned behavior (TPB), this study intends to investigate the impact of students’ mathematical attitude determinants (i.e., attitude, subjective norms, and perceived behavioral control) on intentions, behavioral engagement, and mathematical performance. The data collected online in China’s context and the research hypotheses are developed and then tested through structural equation modeling. It is found that attitude and subjective norms have effects, directly or indirectly, on intentions, behavioral engagement, and mathematical performance. In addition, the intentions have a significant effect on behavioral engagement, and behavioral engagement does likewise on mathematical performance. It has also been accepted that perceived behavioral control is not directly related to intentions but largely to behavior and indirectly to mathematical performance through behavior alone. In conclusion, this study’s findings will contribute to the current literature on mathematical performance and will also inform the policymakers of the proposal on students’ mathematics belief and attitude interventions as a means to improving students’ mathematical performance.